Indonesian Electoral Behaviour : A Statistical Perspective - Ananta, Aris; Suryadinata, Leo; Nurvidya Arifin, Evi (Book collections on Project MUSE., 2004)
In Indonesia's plural society, ethnicity and religion are often considered as two important independent variables to explain electoral behaviour. Many writers have used qualitative methods to relate the performance of political parties in terms of ethnicity and religion. This book questions these assumptions by looking at up-to-date data on the 1999 election and the 2000 population census. The authors, researchers from the Institute of Southeast Asian Studies in Singapore, statistically examine the strength of the impact of religious and ethnic variables relative to those of socio-economic variables (education, per capita income, migration, urbanization, and poverty) on the electoral behaviour of the seven major political parties. Their analysis and findings, together with detailed population profiles in terms of religion, ethnicity and socio-economic conditions at the provincial and district levels, throws light on not only the 1999 election but also the forthcoming 2004 election and beyond. This is the 2nd book in the ISEAS Series, Indonesia's Population.